U.S. Department of Energy's Mine Roof Simulator: Performance Evaluation of Longwall Roof Supports - Robert J. Evans; Paul M. Yavorsky; Fuad S. Maayeh (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1982)
A description and capabilities of the Mine Roof Simulator at the Pittsburgh Mining Technology Center is illustrated for testing longwall roof support equipment. This unique Mine Roof Simulator has the capacity to exert 3 million lbs. of compressive force vertically and 1.6 million lbs. of force horizontally to simulate loads on hydraulic supports typically found in longwall mining. The supports that undergo testing are instrumented with strain gauges and photoelastic coatings such that critically strained areas become readily apparent. These critically strained areas are redesigned or retrofitted with appropriate reinforcement and retested. A data base will be accumulated from several support designs that will lead to an optimized design that will have the potential to reduce downtime by malfunctions of supports and thus increase productivity. A typical test procedure and analysis is given for a two leg 350 ton shield along with a description for placement of strain gauges, displacement gauges, and hydraulic pressure monitors for critical sites.